2006
DOI: 10.1071/fp06079
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional snapshots provide insights into the molecular basis of arbuscular mycorrhiza in the model legume Medicago truncatula

Abstract: Abstract. The arbuscular mycorrhizal (AM) association between terrestrial plants and soil fungi of the phylum Glomeromycota is the most widespread beneficial plant-microbe interaction on earth. In the course of the symbiosis, fungal hyphae colonise plant roots and supply limiting nutrients, in particular phosphorus, in exchange for carbon compounds. Owing to the obligate biotrophy of mycorrhizal fungi and the lack of genetic systems to study them, targeted molecular studies on AM symbioses proved to be difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…Among the core set of AM-related genes, 15 wellknown AM expression markers (Hohnjec et al, 2006;Kü ster et al, 2007b) were identified as strongly induced in our conditions ( Table I). As an example, the MtPt4 gene encoding a phosphate transporter known to be required for an efficient AM symbiosis (Javot et al, 2007) was activated more than 1,000 (log 2 = 10.02)-and 400 (log 2 = 8.65)-fold in G. intraradices-and G. mosseae-colonized roots, respectively.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Among the core set of AM-related genes, 15 wellknown AM expression markers (Hohnjec et al, 2006;Kü ster et al, 2007b) were identified as strongly induced in our conditions ( Table I). As an example, the MtPt4 gene encoding a phosphate transporter known to be required for an efficient AM symbiosis (Javot et al, 2007) was activated more than 1,000 (log 2 = 10.02)-and 400 (log 2 = 8.65)-fold in G. intraradices-and G. mosseae-colonized roots, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…FDR-corrected P values (FDR-P) are indicated. References for the AM-induced genes identified are as follows: MtPt4 (Javot et al, 2007), MtMyb1 (Liu et al, 2003), MtTi1 (Grunwald et al, 2004), MtLec7 (Frenzel et al, 2005), MtGst1 (Wulf et al, 2003), MtBcp1 (Hohnjec et al, 2005), MtLec5 (Frenzel et al, 2005), MtGlp1 , MtHa1 (Krajinski et al, 2002), MtScp1 (Liu et al, 2003), MtVapyrin (Pumplin et al, 2010), MtSbtM1 (Takeda et al, 2011), MtZip7 (Burleigh et al, 2003), MtAnn2 , and MtDxs2 (Floss et al, 2008 roots (Liu et al, 2003;Wulf et al, 2003;Hohnjec et al, 2006;Kü ster et al, 2007b;Guether et al, 2009). Interestingly, the categories membrane transporters, signaling, and TFs were not only prominent but their members were also expressed most significantly different from others in AM roots (data not shown), based on statistical analyses implemented in MapMan (Usadel et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Liu et al 2003;Hohnjec et al 2006). The AM symbiosis association enables a carbon supply for the fungus and an enhanced supply of mineral nutrients, notably phosphorus, to the plant (Liu et al 2003;Hohnjec et al 2006).…”
Section: The Arbuscular Mycorrhizal Legume Symbiosismentioning
confidence: 99%